Assessment and diffusion of medical innovations in France: an overview - Amélie Dubromel; Loïc Geffroy; Gilles Aulagner; Claude Dussart (Taylor & Francis Group, 2018)
Background: In France, a significant part of health expenditure is publicly funding. This put a heavy burden on society. In an economic context requiring tight control of public spending, it seems relevant to control the diffusion of medical innovations. That is why health technology assessment is subject to an increasing interest at national level for management and approval decisions. This article provides an overview of the assessment and diffusion of medical innovation in France. Method: The data are extracted from French authorities or organisations websites and documents and from French legislative texts. In addition, regarding discussion, a search in MEDLINE database was carried out. Results: An overview of the assessment and diffusion of medical innovation in France is given by presenting the different types of medical innovations according to French health system definition (I); introducing French authorities participating to health technology assessment and describe assessment procedures of medical innovations (II); and giving details about market access process of innovative health product in France (III). Key opportunities and challenges of medical innovation assessment and diffusion in France are discussed at the end of this article. Conclusion: In France, medical innovation is considered as a crucial component for quality of care and performance of healthcare system. The aim of health technology assessment is to promote a secure and timely access to innovation for patients. Nevertheless, it appears necessary to improve regulatory mechanisms.